Pengaplikasian Teknologi Digital dalam Pembelajaran PAI dan Bahasa Arab - Tugino Tugino; Muhammad Munadi; Khuriyah Khuriyah (Innovative: Journal Of Social Science Research, 2023)
Digital technology for learning PAI (Islamic Religious Education) and Arabic has not been used optimally. This is because there are still teachers who teach monotonously using the lecture method in delivering material in class without using the media. The method in this research uses literature study. Data was obtained through various sources consisting of journals and books. For data analysis using descriptive analysis. The results of the study show that learning PAI and Arabic using digital technology provides benefits for teachers and students. The benefits of its application for teachers and students provide convenience in accessing various learning resources, making learning more interactive, learning can be done anytime and anywhere, and learning can be done remotely.